Unravelling the Versatile Nature of Pseudomonas aeruginosa: Challenges and Innovations in Infection Management - Alharbi, Mohanned Talal (Journal of King Abdulaziz University: Medical Sciences, 2024)
This review delves into the intricate and multifaceted nature of Pseudomonas aeruginosa, a notorious pathogen known for its adaptability, virulence, and resistance mechanisms. P. aeruginosa presents formidable challenges in both healthcare and community settings due to its ability to thrive in diverse environments, form biofilms, and acquire antibiotic resistance. The range of infections it causes, varying from mild to severe, highlights the urgent need for effective management strategies. Key aspects of P. aeruginosa pathogenesis, transmission, and associated risk factors are discussed, underscoring the significance of infection control measures, particularly in healthcare settings. The emergence of multidrug-resistant strains further emphasizes the necessity for innovative treatment approaches. Alternative therapies, including phage therapy, antimicrobial peptides, and natural products, offer promising avenues for combatting P. aeruginosa infections, especially those caused by multidrug-resistant strains. Additionally, antibiotic combination therapy, incorporating antivirulence compounds, demonstrates potential in both treating infections and curbing the spread of antibiotic resistance. Despite these promising alternatives, challenges persist in the development and implementation of these approaches, encompassing efficacy, safety, and regulatory considerations. Further research, experimentation, and clinical trials are imperative to refine these strategies and address the ongoing threat posed by P. aeruginosa and other multidrug-resistant organisms. In summary, this review provides valuable insights into the current challenges and advancements in managing P. aeruginosa infections, with a specific focus on exploring novel therapeutic options and enhancing patient outcomes. Continued efforts in research and development are paramount for effectively combating this formidable pathogen and mitigating its impact on public health.